Entre redes: juventudes, ambientes virtuais e vidas entretidas - Barreiro, Rafael Garcia (2019)
Assuming that digital social networks have a great impact on contemporary society, as a means of circulating information, opinion and influence; there is a correlation between digital networks, the transmission of information through digital influencers and the daily lives of young people towards the established social organization. From the theoretical assumptions of social occupational therapy, specifically affiliated with the methodological current of historical materialism proposed by Brazilian occupational therapists in the 1980s, this analysis is proposed in the understanding of juvenile lifestyles and the impact of digital platforms in the stylization processes of life. The purpose of this thesis was to analyze and discuss the use of digital social networks and their presence on issues related to youth daily life and their ways of life, through digital influencers, personalities who publish constant content directed to young people. The methodology was based on the resource of netnography, which uses the theoretical foundations of ethnography in digital environments. The empirical field consisted of three phases: interviews with communication professionals; youth activity workshops in Brazil and Portugal; conducting netnographs with the five most cited digital influencers in previous phases, specifically through video analysis of young digital influencers posted on YouTube. As a result, the interviews showed the marketing strategies linked to the digital influencers. In the workshops, young people demonstrated how digital platforms are related to their daily lives, identifying humor, sports and music as the content they most view and share on networks, and also indicated digital influencers of their preferences. The netnographs were developed with five digital influencers, namely: Whindersson Nunes, Julio Cocielo, Dani Russo, Felipe Neto and Niina Secrets; seen as "celebrities" of virtual spaces, as well as a process of professionalization in being a "youtuber". With this professionalization, alignment with the market and the purchase of consumer goods was evident in all influencers who practice a direct relationship between product and consumption, in advertising and marketing strategies. The results showed that digital influencers have a significant share of representativeness in the contemporary youth universe of varied cultural, social and economic contexts, promoting debates and influences in decision making about lifestyles. From the netnographic analysis, together with the other phases of the empirical field, it can be concluded that the results show that the influencers are configured as communicators within a mass culture, which stimulates consumption and influence juvenile ways of life, conveying content with low criticality and high conservative value. The work sought, from the perspective of social occupational therapy, the work sought to understand the Internet as a socio-technique of virtual environments influencing youth lifestyles.